2006
DOI: 10.1007/s00359-005-0090-5
|View full text |Cite
|
Sign up to set email alerts
|

Spatial contrast sensitivity of birds

Abstract: Contrast sensitivity (CS) is the ability of the observer to discriminate between adjacent stimuli on the basis of their differences in relative luminosity (contrast) rather than their absolute luminances. Prior to this study, birds had been thought to have low contrast detection thresholds relative to mammals and fishes. This was a surprising phenomenon because birds had been traditionally attributed with superior vision. In addition, the low CS of birds could not be explained by retinal or optical factors, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(89 citation statements)
references
References 185 publications
8
78
0
Order By: Relevance
“…By way of comparison, humans can detect contrast differences as low as 0.6% (De Valois and Morgan, 1974), but spatial resolution decreases more than eleven times as contrast goes down from 100% to 0.6%. In birds, resolution decreases more than six times as contrast goes down from 100% to 7-14% depending on the species (Reymond and Wolfe, 1981;Ghim and Hodos, 2006;Harmening et al, 2009;Jarvis et al, 2009;Lind et al, 2012). If we assume a similar decrease in spatial resolution for our study species as in other birds, then Leach's storm petrels would be able to detect lowest contrast with a spatial resolution of 1.1 cycles deg −1 , whereas northern fulmars would do so with a resolution of 7.2 cycles deg −1 .…”
Section: Assessing Differences In Visual Ability In Real-world Scenariosmentioning
confidence: 70%
See 1 more Smart Citation
“…By way of comparison, humans can detect contrast differences as low as 0.6% (De Valois and Morgan, 1974), but spatial resolution decreases more than eleven times as contrast goes down from 100% to 0.6%. In birds, resolution decreases more than six times as contrast goes down from 100% to 7-14% depending on the species (Reymond and Wolfe, 1981;Ghim and Hodos, 2006;Harmening et al, 2009;Jarvis et al, 2009;Lind et al, 2012). If we assume a similar decrease in spatial resolution for our study species as in other birds, then Leach's storm petrels would be able to detect lowest contrast with a spatial resolution of 1.1 cycles deg −1 , whereas northern fulmars would do so with a resolution of 7.2 cycles deg −1 .…”
Section: Assessing Differences In Visual Ability In Real-world Scenariosmentioning
confidence: 70%
“…barn owl (Tyto alba), wedge-tailed eagle, chicken, pigeon (Columba livia), parrots], birds have been shown to have lower contrast sensitivity compared with humans and some other mammals (summary in Lind et al, 2012). The minimum contrast birds can detect ranges from 7 to 14% (Reymond and Wolfe, 1981;Ghim and Hodos, 2006;Harmening et al, 2009;Jarvis et al, 2009;Lind et al, 2012). By way of comparison, humans can detect contrast differences as low as 0.6% (De Valois and Morgan, 1974), but spatial resolution decreases more than eleven times as contrast goes down from 100% to 0.6%.…”
Section: Assessing Differences In Visual Ability In Real-world Scenariosmentioning
confidence: 99%
“…The Weber fraction for human LWS cone photoreceptors has been suggested to be 0.018 (Wyszecki and Stiles, 2000), which is much smaller than the Weber fraction for bird LWS cones (0.06 for chickens and 0.1 for Leiothrix and budgerigars). This difference could explain why we found no obvious difference in colour discrimination threshold between humans and birds and may also help to explain why birds generally have lower contrast sensitivity than humans (Ghim and Hodos, 2006;Gover et al, 2009;Harmening et al, 2009;Lind et al, 2012).…”
Section: Dark Noisementioning
confidence: 72%
“…Harmening et al (2009) found a contrast sensitivity peak of 1-2 cpd and visual acuity of 3-4 cpd. Ghim and Hodos (2006) used pattern electroretinography to compare the CSF of several bird species, including falcons (Falco sparvarius), owls (Tyto alba), European starlings (Sturnus vulgaris), quails (Coturnix coturnix japonica), red-bellied woodpeckers (Melanerpes carolinus), and pigeons (Columbia livia). They found that these birds had a band-pass CSF that peaked at 3 cpd (falcon), 1-2 cpd (pigeon, starling, and owl), 0.8-1 cpd (quail), and 0.5-0.7 cpd (woodpecker).…”
Section: Luminance Spatial Contrast Sensitivity Of Birdsmentioning
confidence: 99%